The Effect Of Budget Participation, Budget Target Clarity and Authority Transfer on Managerial Performance - Bonifasius H. Tambunan (International Journal Reglement & Society (IJRS), 2021)
The purpose of this study was to determine and analyze the effect of participation in budgeting, clarity of budget targets, and delegation of authority on managerial performance in the North Tapanuli Regency Government. This type of research is causality. The analysis used is multiple linear analysis. The research instrument test consisted of validity and reliability tests. The classical assumption test consists of normality test, heteroscedasticity test and multicollinearity test. Hypothesis testing consists of the f test (simultaneous test), t test (partial test) and determinant coefficient test (R2). The results of this study indicate that budgetary participation, clarity of budget targets, and simultaneous delegation of authority have a significant effect on managerial performance. Budgeting participation has a positive and significant effect on managerial performance. Clarity of targets has a positive and insignificant effect on the budget on managerial performance. The delegation of authority has no effect on managerial performance. and simultaneous delegation of authority have a significant effect on managerial performance. Budgeting participation has a positive and significant effect on managerial performance. Clarity of targets has a positive and insignificant effect on the budget on managerial performance. The delegation of authority has no effect on managerial performance. and simultaneous delegation of authority have a significant effect on managerial performance. Budgeting participation has a positive and significant effect on managerial performance. Clarity of targets has a positive and insignificant effect on the budget on managerial performance. The delegation of authority has no effect on managerial performance.